Pengembangan Desain Edukatif pada Buku Tabungan Anak dengan Pendekatan Quality Function Deployment - Aisyah Fitria; Zulkarnain Zulkarnain; Emmidia Djonaedi (Pusat riset dan Inovasi Nasional, 2025)
The 2024 National Financial Literacy and Inclusion Survey shows that many Indonesians still do not understand financial fundamentals. This condition contributes to difficulty in managing personal finances. Therefore, financial education from an early age is needed to help people develop healthy financial habits. One effective medium for delivering financial education is a children’s savings book. However, most available savings books are less attractive and do not align with children’s preferences. This study aims to develop a children’s savings book design by integrating educational elements, such as a temporary money storage, based on users’ preferences. The Quality Function Deployment (QFD) approach was used to translate customer needs into product visualization. Data were collected through expert discussion, interviews, and questionnaires distributed using purposive sampling. The results show that the highest-priority feature for further development is the temporary money storage integrated into the book’s cover. This element was then incorporated into the children’s savings book design, while considering both functional and educational aspects.